A Simple Architecture for Implementation of 8 - point Discrete Cosine Transform - Priyabrata Mohapatra, Sudhansu Sekhar Nayak, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
An architecture for implementation of 8 - point discrete cosine transform (DCT) is suggested in this paper. The architecture is simple and suitable for VLSI implementation. The hardware time and area complexities are It has less number of multipliers.